NARASI DI BALIK JERUJI : STUDI KUALITATIF MENGENAI PEMAKNAAN DIRI DAN KESEJAHTERAAN PSIKOLOGIS WARGA BINAAN MELALUI INTERVENSI STORYTELLING - Shafly, Mochamad Ibadirohman; Moh. Fikri Tanzil Mutaqin; Ahmad Fauzi; Yosi Asri Bandrio (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the role of storytelling intervention on the sense of self and psychological well-being of inmates at Rangkasbitung III Penitentiary. Inmates often experience psychological stress, social stigma, guilt, and difficulty in rebuilding their identity during their sentence. Therefore, this study aims to explore how storytelling can be a medium for emotional expression, self-reflection, and identity reconstruction in inmates. This study applies a descriptive qualitative approach involving ten inmates who were selected purposively. Data were collected through observation, semi-structured interviews, and documentation during the storytelling activity, then analyzed using thematic analysis to identify themes related to emotional catharsis, self-awareness, and resilience development. The results showed that storytelling helped participants express sadness, regret, and heartache regarding life experiences and criminal acts they had committed. This activity also helped inmates reflect on life experiences, rebuild their sense of self, and develop a more positive outlook on the future. In addition, storytelling created a supportive atmosphere that encouraged emotional openness and psychological adaptation of participants. This study concludes that storytelling has potential as a psychosocial rehabilitation approach to support the psychological well-being and identity transformation of inmates in correctional settings.